UJI DIAGNOSTIK LIMFOSIT ATIPIKAL TERHADAP ANTIBODI IgM DAN IgG ANTI DENGUE DALAM DIAGNOSIS INFEKSI DENGUE DI RSPAD GATOT SOEBROTO TAHUN 2016-2019 - Luh Ayu Laura Maharani Mardika, (2021)
Dengue infection is a disease caused by dengue virus and an emerging disease due to global climate change. The most preferred examination at this time which is used as main reference is anti dengue IgM & IgG antibody test. Atypical lymphocyte in peripheral blood examination is a supporting tool in the diagnosis of dengue infection, especially in remote areas because it used simple equipment. The aim of this study was to see the diagnostic value of atypical lymphocyte towards anti dengue IgM & IgG antibodies. This study was an analytic observational study using cross-sectional design with diagnostic test. The sample of this study were patients who were treated in the inpatient room at RSPAD Gatot Soebroto whose fulfilled the inclusion and exclusion criteria. The number of samples was 40 people obtained from the medical records of patients with dengue infection at RSPAD Gatot Soebroto in 2016-2019 and analyzed using 2x2 diagnostic table test. The result was atypical lymphocyte established sensitivity of 75%, specificity of 35,7%, and accuracy of 67.5%. The conclusion of this study was atypical lymphocyte can help diagnose dengue infection but can not replace the anti dengue IgM and IgG antibodies. Keywords : Dengue infection, atypical lymphocyte, anti dengue IgM and IgG, sensitivity, and specificity